Distribution and abundance of zooplankton in Muttukadu backwater, Chennai - NS, Bharathi Devi; R, Ramanibai (Journal of Research in Biology, 2012)
The present work aims to study the zooplankton distribution and abundance in Muttukadu backwater, Chennai, East coast of India from December 2008 to May 2010. We have recorded 46 species of which, 31 species belongs to copepoda, 9 species belongs to Rotifera, 2 species belongs to Ostracoda, four species of Cladocera. Among zooplankton, particularly Rotifera was the dominant group throughout the study period and highest count was recorded in the month of January, 2008. Percentage composition and Shannon diversity index is also presented for zooplankton community.